Proses Pengeringan Lengkuas Merah (Alpinia purpurata) Menggunakan Pengering Hybrid Tipe Rak dan Sifat Fisik Bubuk yang Dihasilkan - Aprilia, Sella; Tamrin, Tamrin; Novita, Dwi Dian; Warji, Warji (abe.fp.unila.ac.id, 2026)
Indonesia is estimated to have 100 to 150 plant families, one type of plant that is widely used by Indonesian people as one of the spices is galangal. Fresh galangal rhizomes contain high water, so post-harvest handling efforts are needed to increase the shelf life of galangal. The rack-type hybrid drying house is an alternative technology for drying agricultural products. The purpose of this study was to test the rack-type hybrid drying house for drying red galangal. This drying was carried out with three treatments with three repetitions, namely drying using a rack-type hybrid drying house, drying using an oven and drying using direct sunlight. Observations made to determine the physical properties of the resulting red galangal powder include measuring colour, measuring bulk density, measuring stack angle, measuring water absorption, and the degree of fineness of the material. Drying red galangal to reach 10% water content in drying using a rack-type hybrid dryer takes 17 hours, drying using an oven takes 13 hours and drying using solar energy takes 25 hours. Temperature and drying treatment affect the density value of red galangal powder.